PROSPEK PUBLIC SPACE PADA KAMPUNG SUSUN SEBAGAI RUANG INTERAKSI SOSIAL, EKONOMI DAN PENGEMBANGAN ILMU DI AREA BANTARAN SUNGAI - Mulyandari, Hestin; Bhayusukma, Muhammad Yani (Semarang State University, 2015)
Commercial buildings in the city of Yogyakarta is growing rapidly and removing settlements outside the city of Yogyakarta. Some settlements reject commercial buildings, besides there is a plan of Ministry of public housing about the proposed location of settlements in the city of Yogyakarta to serve flats to maintain residential land and provide homes for low-income people. This study aims to explore the needs of the needs of the public space for children, adults, and the elderly. This study uses research methods - explorative search were the findings of the survey location, land use policy along the riverbank, and the use of public spaces in the building. RW 07 Jetis Harjo has become one of the targeted land for flats. Components of flats should enter